Correction: Segmentation of HE-stained meningioma pathological images based on pseudo-labels. - Chongshu Wu; Jing Zhong; Lin Lin; Yanping Chen; Yunjing Xue; Peng Shi (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0263006.].